Fenomena Underpricing pada Penawaran Umum Perdana di Bursa Efek Jakarta Periode 1998-2005 - Sri Isworo Ediningsih; C. Ambar Pujiharjanto (Jurnal Manajemen Maranatha, 2007)
It is now widely accepted that initial public offerings (IPOs) of common stocks offer large abnormal return on their first day of trading. As reported in Lougran et.al. (1994), this phenomenon of short-run underpricing has been experienced in every country with a stock market. In this paper, we empirically investigate Indonesian initial public offerings (IPOs) to provide one case of the international evidence on underpricing phenomenon. Using a sample of 84 IPOs listed on Jakarta Stock Exchange during 1998-2005 period and market adjusted return approach, this studies can be proved underpricing at firstly traded in the Stock Exchange. We also find, based on holding period (1 day – 1 month trading) the Jakarta Stock Exchange is not semistrong-form efficiency categorized.